PENGARUH KEPERCAYAAN DAN CITRA TERHADAP LOYALITAS YANG DIMEDIASI OLEH KEPUASAN PADA MAHASISWA ANGKATAN 2018 DI INDUSTRI PENDIDIKAN UNIVERSITAS SYIAH KUALA - Doni Agam; Sayed Mahdi (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study aims to determine The Effect Of Trust And Image On Loyalty Mediated By Satisfaction In Class Of 2018 Students in the Syiah Kuala University Education Industry. The research respondents were 248 people, namely active Class Of 2018 students in the Syiah Kuala University. Data collection was carried out by distributing questionnaires directly to respondents in July to August 2022. This study used a Proportional Random Sampling method where the sample was taken randomly. The analytical method used is Structural Equation Modelling (SEM) AMOS application, and the mediating effect was tested using the Sobel Test. The results of the analysis show that Trust and Image have a significant effect on Loyalty, and Satisfaction has a significant effect on Loyalty, and Satisfaction partially mediates the relationship between Trust And Image On Loyalty.